2018
DOI: 10.1002/jhet.3134
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzazolyl Pyrimidines Under Ultrasonication and Their Antimicrobial Activity

Abstract: in Wiley Online Library (wileyonlinelibrary.com).(1) The benzoxazolyl/benzothiazolyl/benzimidazolyl pyrimidines were prepared under ultrasonication in the presence of pyridine/dimethylaminopyridine and triethylamine. (2) Better yields were recorded in 4-(N,N-dimethylamino)pyridine and Et 3 N. (3) The presence of electron withdrawing chloro, bromo, and nitro substituents enhanced antimicrobial activity (13c, 13e, 14e: minimum inhibitory concentration = 6.25 μg/well against Bacillus subtilis; 13e, 14e: minimum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Next, novel benzoxazolyl, benzothiazolyl and benzimidazolyl pyrimidines derivatives were synthesized and evaluated by Kayathi et al [21] Among them, compounds 23 and 24 (Figure 4) with benzothiazolyl and benzimidazolyl groups, respectively, both exhibited the equivalent potent activity against B. subtilis and A. niger compared to that of standard drug chloramphenicol and ketoconazole. The electron-withdrawing groups such as nitro group on the benzene ring was found to increase the activity.…”
Section: Monopyrimidine Trisubstituted Derivativesmentioning
confidence: 99%
“…Next, novel benzoxazolyl, benzothiazolyl and benzimidazolyl pyrimidines derivatives were synthesized and evaluated by Kayathi et al [21] Among them, compounds 23 and 24 (Figure 4) with benzothiazolyl and benzimidazolyl groups, respectively, both exhibited the equivalent potent activity against B. subtilis and A. niger compared to that of standard drug chloramphenicol and ketoconazole. The electron-withdrawing groups such as nitro group on the benzene ring was found to increase the activity.…”
Section: Monopyrimidine Trisubstituted Derivativesmentioning
confidence: 99%
“…It has been reported that pyrimidine and its fused pyrimidine derivatives are a class of heterocyclic scaffolds that possess a range of biological and pharmacological activities, 1 for example, anticancer, 2 antimicrobial, 3 antioxidant, 4 antidepressant, 5 antiviral, 6 and anxiolytic activities. 7 Because of the extensive pharmacological and biological activities of pyrimidine, 8 the action targets of pyrimidine were conducted in-depth studies.…”
Section: Introductionmentioning
confidence: 99%